Integrasi Realistic Mathematics Education, Culturally Responsive Teaching, dan Artificial Intelligence untuk Keterampilan 4C Abad 21: Sebuah Tinjauan Sistematis - Sondang Noverica; Sinta Dameria Simanjuntak (FKIP Universitas PGRI Palembang, 2026)
This study aims to systematically review the literature on Realistic Mathematics Education (RME), Culturally Responsive Teaching (CRT), Artificial Intelligence (AI), and 21st-century skills (4C) to identify and bridge research gaps in mathematics education. The research employed a Systematic Literature Review (SLR) combined with bibliometric analysis using the PRISMA protocol and supported by VOSviewer and Biblioshiny software. From the Scopus database, 79 articles met the inclusion criteria and were analyzed based on publication trends, author collaboration networks, citation structures, and qualitative synthesis. The findings indicate a significant increase in research on RME and AI over the past decade, while the integration of CRT remains limited despite its philosophical alignment with RME. This study identifies five major research gaps—namely theoretical, empirical, methodological, population, and evidential. The integration of RME, CRT, and AI has strong potential to form an adaptive, contextual, and culturally responsive mathematics learning model that strengthens 21st-century competencies. These findings provide new directions for developing inclusive and technology-based mathematics education.